2012
DOI: 10.31931/fmbc.v15i2.2012.83-98
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater Mussels of the Powell River, Virginia and Tennessee: Abundance and Distribution in a Biodiversity Hotspot

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(35 citation statements)
references
References 8 publications
0
33
2
Order By: Relevance
“…This idea also applies to the Powell River, where TDS concentrations are substantially higher in the upper reaches of the river and mussel populations have experienced long-term declines at monitoring locations downstream of these high TDS reaches (Ahlstedt et al, 2005;Johnson et al, 2012). However, our findings do not support the suggestion that chronic toxicity of major ions is the primary cause of declining mussel populations in these rivers.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…This idea also applies to the Powell River, where TDS concentrations are substantially higher in the upper reaches of the river and mussel populations have experienced long-term declines at monitoring locations downstream of these high TDS reaches (Ahlstedt et al, 2005;Johnson et al, 2012). However, our findings do not support the suggestion that chronic toxicity of major ions is the primary cause of declining mussel populations in these rivers.…”
Section: Discussioncontrasting
confidence: 62%
“…Long-term water quality monitoring of the Clinch and Powell Rivers has documented increasing temporal trends of TDS concentrations since the 1960s (Price et al, 2011(Price et al, , 2014. Independent biological monitoring, initiated in 1979, has documented significant declines of freshwater mussel richness and density in sections of Clinch River and throughout the Powell River (Ahlstedt et al, 2005;Johnson et al, 2012;Jones et al, 2014). Recent research has found a spatial association between elevated TDS concentrations and declining freshwater mussel populations in the Clinch River; reaches of the river experiencing the greatest declines in mussel richness and density have elevated concentrations of major ions relative to other reaches of the river where mussel populations are stable (Johnson et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Rivers draining Appalachian mined areas include the Powell River of southwestern Virginia and northeastern Tennessee, which hosts exceptional biological richness and a high diversity of at-risk species that include multiple freshwater mussels (Johnson et al, 2012;Ahlstedt et al, 2005). Freshwater mussels (Unionidae) occur worldwide but achieve their greatest diversity in North America, especially in southeastern USA (Lydeard et al, 2004).…”
Section: Introductionmentioning
confidence: 99%